PUBLIC PERCEPTION OF SOCIO-ECONOMIC TRANSFORMATION IN SAUDI ARABIA: THE CASE OF THE NEW MURABBA PROJECT - Nadiya Azahra Hidayat; Siti Rohmah Soekarba (CMES (Center of Middle Eastern Studies), 2024)
The rapid economic development of Saudi Arabia reflects the country's commitment to achieving its Vision 2030 objectives. Vision 2030 encompasses transformative policies aimed at diversifying the economy and modernizing society. However, its implementation has been accompanied by significant political and social challenges, including resistance within the Kingdom. This study examines public perceptions of Vision 2030, focusing on the New Murabba Project as a case study. Using content analysis of social media platforms, this research identifies two distinct community groups with differing responses. The first group, consisting of young professionals and progressive citizens, supports the project as a necessary reform for economic diversification. In contrast, the second group, dominated by older and conservative religious communities, expresses concerns about potential cultural and religious implications. This study finds the duality of public opinion and underscores the importance of balancing modernity with traditional values to ensure the inclusivity of national policies.